Political Education and Social Engineering in an Emerging Democracy - Oladipo, Temidayo David (African Journal of Stability and Development (AJSD), 2018)
This work discusses the role that political education has to play in an emerging democracy just opening up to the entrenchment of democratic principles. Such a democracy is often faced with some challenges; one being that its past is plagued with features that are antithetical to the principles of democracy such that if care is not taken, these anomalies will smoother democratic institutions, practices and underlying philosophies. The second one identified in the paper is that moral principles are not adhered to in such a democracy. There is consequently the need for social engineering to correct the deficiencies. Political education is projected as a bulwark for strengthening democracy in societies where the concept is just finding its feet. It is through political education that, citizens can be imparted with necessary lessons regarding politics, democratic ethos and democratic institutions. Political education will aid the acculturation of citizens of emerging democracies in democratic norms and moral values.